Articuler construction des savoirs, pratiques écrites et orales au lycée : le rôle du débat interprétatif délibératif en classe de français - Marie-France Rossignol; Brigitte Marin (Recherches en Éducation, 2011)
Despite recommendations outlined in educational curricula over the last decade, the spoken debate form has struggled to establish itself as a standard practice in education. The use of spoken debates has suffered considerably from the contaminating effects of social practices that fail to ensure effective learning (such as media debates). Yet the debate form has many advantages (particularly in French). Provided they are linked to subject-specific objectives, are based on more constructive social practices, and are incorporated as a standard and highly regulated practice, spoken debates foster the development of a wide range of skill-sets in a context in which differences between pupils tend to be reduced. Based on an analysis of a prototypical deliberative debate conducted in seconde (first year of lycée, or French sixth form college), this paper shows how spoken debates create a safe collaborative space of exchange and encourage lycée pupils to adopt a reflexive attitude that supports learning (particularly in dialogic and interactional areas). While the high-level cognitive activity targeted by spoken debates cannot meet the demands of all learning objectives, the debate form consolidates subject-specific and cross-disciplinary knowledge and skills on a more egalitarian basis. More specifically, spoken debates foster the development of specialized literary reading skills and broader social and civic skills that subtend the process of individual identity construction in a group class context.